Synthesis and application of polypyrrole/carrageenan nano-bio composite as a cathode catalyst in microbial fuel cells - Esmaeili, Chakavak; Ghasemi, Mostafa; Lee, Yook Heng; Hassan, Sedky H. A.; Abdi, Mahnaz M.; Wan Daud, Wan Ramli; Ilbeygi, Hamid; Ismail, Ahmad Fauzi (Elsevier, 2014)
A novel nano-bio composite polypyrrole (PPy)/kappa-carrageenan(KC) was fabricated and characterized for application as a cathode catalyst in a microbial fuel cell (MFC). High resolution SEM and TEM verified the bud-like shape and uniform distribution of the PPy in the KC matrix. X-ray diffraction (XRD) has approved the amorphous structure of the PPy/KC as well. The PPy/KC nano-bio composites were then studied as an electrode material, due to their oxygen reduction reaction (ORR) ability as the cathode catalyst in the MFC and the results were compared with platinum (Pt) as the most common cathode catalyst. The produced power density of the PPy/KC was 72.1 mW/m2 while it was 46.8 mW/m2 and 28.8 mW/m2 for KC and PPy individually. The efficiency of the PPy/KC electrode system is slightly lower than a Pt electrode (79.9 mW/m2) but due to the high cost of Pt electrodes, the PPy/KC electrode system has potential to be an alternative electrode system for MFCs.